Clinical treatment outcomes of deciduous molar vital pulp therapy at School of Dental Sciences, Universiti Sains Malaysia - Maqbool, Manahil (2020)
Vital pulp therapy (VPT) aims to manage teeth with only part of the compromised dental pulp without the extirpation of the entire healthy pulp tissue. It targets at retaining deciduous teeth until their normal exfoliation. To date, very limited studies have compared the treatment outcomes of indirect pulp therapy (IPT) and ferric sulphate pulpotomy (FSP) carried out on deciduous molar(s) (DM). Thus, this retrospective study aimed to determine, the clinical treatment outcomes of VPT performed on paediatric DM at School of Dental Sciences, HUSM. Clinical records of 590 patients with 600 DM treated with IPT and FSP were reviewed. 342 DM underwent IPT and 258 FSP. All patient records which had information about DM treated with VPT, were included. Records of patients under 4 and above 8 years of age were excluded, along with those records in which VPT was performed on teeth other than DM. Association of treatment type (IPT/FSP), tooth type (1st or 2nd DM), arch location (maxillary/mandibular) and number of carious surfaces involved (one or multiple) to successful outcomes was analysed. Logistic regression analysis was used for statistical analysis with significance level set at P < 0.05. A total number of 278 1st DM and 322 2nd DM underwent IPT and FSP. Based on arch location, 234 were maxillary DM and 366 were mandibular DM. According to carious surfaces involved, 363 DM had one surface destroyed by caries and 237 DM had multiple surfaces destroyed. There was a significant difference based on the type of treatment performed (P=0.036), i.e., the odds of IPT being successful were two times more than those of FSP. Also, there was asignificant difference according to tooth type (P<0.05) and arch location (P=0.003), i.e., the odds of 2nd DM having successful outcomes were 4 times more than 1st DM. Additionally, the odds of maxillary molars having successful outcomes were 3 times more than when compared to their mandibular counterparts. However, there was no significant difference in success rates based on carious surfaces involved (P=0.873). In conclusion IPT showed a higher success rate than FSP, with 2nd DM having a better overall prognosis than 1st DM. Maxillary DM had a better prognosis than their mandibular counterparts, while comparing the two VPT.